2019
DOI: 10.1371/journal.pone.0223590
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of porcine bone marrow-derived dendritic cells induced by GM-CSF

Abstract: In vitro generation of dendritic cells (DCs) is advantageous for overcoming the low frequency of primary DCs and the difficulty of applying isolation techniques for studying DC immunobiology. The culture of bone marrow cells with granulocyte-macrophage colony-stimulating factor (GM-CSF) has been used extensively to generate bone marrow-derived dendritic cells (BMDCs). Studies have reported the heterogeneity of cells grown in murine GM-CSF culture based on the levels of MHCII expression. Although porcine DCs ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…On day 5 of culture an immatureimmunophenotype of the moDCs was obtained however after 48 h of cultivation with LPS from E. coli O111:B4, we observed an increase in surface marker expression for the MHC class II, CD80/86 surface marker (> 45%). Similar results were obtained other available studies which investigated the ability of live pathogens or their PAMPs to induce the maturation and activation of monocyte-derived macrophages and dendritic cells, with similar results (Carrasco et al 2001 ; Kim et al 2019 ; Meital 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…On day 5 of culture an immatureimmunophenotype of the moDCs was obtained however after 48 h of cultivation with LPS from E. coli O111:B4, we observed an increase in surface marker expression for the MHC class II, CD80/86 surface marker (> 45%). Similar results were obtained other available studies which investigated the ability of live pathogens or their PAMPs to induce the maturation and activation of monocyte-derived macrophages and dendritic cells, with similar results (Carrasco et al 2001 ; Kim et al 2019 ; Meital 2019 ).…”
Section: Discussionsupporting
confidence: 89%
“…On the contrary, our cultures were treated with GM-CSF and IL-4, producing MHC-II mid cells that resemble DCs and MHC-II high cells that resemble Macs, according to their immunophenotype, phagocytosis capacity and the expression of signature genes from the DC or Macs lineage. A previous work described that different maturation states were obtained when swine BM precursors were cultured only with GM-CSF (Kim et al, 2019). In pigs, same as in other species, DC maturation is associated with an increase in MHC-II expression, in addition to loss of CD14 expression and decreased phagocytic capacity (Singleton et al, 2016), reason why different states of maturation were are not consistent with the cell cultures analyzed in this work.…”
Section: Discussionmentioning
confidence: 61%
“…The morphology of the cells on the sixth day of culture was observed under a microscope, and obvious cell colonies were observed in each group of cells. The formation of colonies was a sign of the successful induction of monocyte‐derived DCs by GM‐CSF [28]. In addition, the positive rate of rat DC‐specific marker OX‐62 detected by flow cytometry was >95%, which also indicated that the induced DCs had high purity and met the requirements of subsequent experiments.…”
Section: Discussionmentioning
confidence: 99%